Optimization of nutritional supplements for enhanced lactic acid production utilizing sugar refinery by-products - Srivastava A.; Poonia A.; Tripathi A.D.; Singh R.P.; Srivastava S.K. (My University, 2025)
The present study investigated the synergistic effect of nutritional supplements (amino acid and Tween 80) on lactic acid production by Lactobacillus delbruckii utilizing a sugar refinery by product (cane molasses) in a submerged fermentation process. Initially, the effect of individual factors on lactic acid yield was studied by supplementing amino acids and their combinations, Tween 80 and cane molasses at varying concentrations in production medium. A combination of l-phenylalanine and l-lysine gave a maximum lactic acid yield of 47.89∈±∈0.1 g/L on a dry cell weight basis at individual factor level. Similarly, maximum lactic acid yield was obtained by supplementing the production medium with 40.0 g/L and 2.0 g/L Tween 80 and cane molasses, respectively, at individual factor level. In order to further improve the lactic acid yield, nutritional supplements were optimized by central composite rotatable design (CCRD) using Minitab 15 software. Shake flask cultivation under optimized conditions, i.e., cane molasses (32.40 g/L), Tween 80 (2.0 g/L) and l-phenylalanine and l-lysine (34.0 mg/L) gave a lactic acid yield of 64.86∈±∈0.2 g/L, corresponding to 95.0 % of the predicted yield of 67.78∈±∈0.3 g/L. Batch cultivation performed in 7.5 L bioreactor (working volume: 3.0 L) under optimized conditions gave maximum lactic acid yield and productivity of 79.12∈±∈0.2 g/L and 3.40 g/L·h, which is higher than previous studies with reduced fermentation time. Screening of lactic acid producing bacteria and characterization of lactic acid was also done. © 2013 Springer-Verlag Berlin Heidelberg and the University of Milan.